2022
DOI: 10.1111/jre.13069
|View full text |Cite
|
Sign up to set email alerts
|

Impaired autophagy flux by lncRNA NEAT1 is critical for inflammation factors production in human periodontal ligament stem cells with nicotine treatment

Abstract: Background and Objectives Periodontitis is the top reason for tooth loss, and smoking significantly increases severe periodontitis risk. Defective autophagy has been reported to play a vital role in periodontitis. This study aimed to elucidate the relationship between autophagy and inflammation factors production in nicotine‐treated periodontal ligament stem cells (PDLSCs) and the underlying mechanism. Methods In this study, transmission electron microscopy, immunofluorescence, and the mCherry‐GFP‐LC3 plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…Additionally, lncRNA KCNQ1OT1, nuclear enriched abundant transcript 1 (NEAT1), lncRNA LRRC75A-AS1, and HELLPAR are key long non-coding RNAs involved in our ceRNA network to bridge the connection of HGF and periodontitis. KCNQ1OT1 (potassium voltage-gated channel subfamily Q member 1 overlapping transcript 1), a crucial lncRNA in our ceRNA network, is involved in regulating lipid metabolism, atherosclerosis, and in ammation [82]. LncRNA KCNQ1OT1 regulated high glucose-induced proliferation, oxidative stress, ECM accumulation, and in ammation in human glomerular mesangial (HGMC) cells via the miR-147a/SOX6 axis in diabetic nephropathy (DN) [83], LncRNA KCNQ1OT1 can also target miR-214, and regulate ALP, BMP2, Runx2, OPN, and OCN in osteogenesis and related disorders, which may include osteoporosis and periodontitis [84].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lncRNA KCNQ1OT1, nuclear enriched abundant transcript 1 (NEAT1), lncRNA LRRC75A-AS1, and HELLPAR are key long non-coding RNAs involved in our ceRNA network to bridge the connection of HGF and periodontitis. KCNQ1OT1 (potassium voltage-gated channel subfamily Q member 1 overlapping transcript 1), a crucial lncRNA in our ceRNA network, is involved in regulating lipid metabolism, atherosclerosis, and in ammation [82]. LncRNA KCNQ1OT1 regulated high glucose-induced proliferation, oxidative stress, ECM accumulation, and in ammation in human glomerular mesangial (HGMC) cells via the miR-147a/SOX6 axis in diabetic nephropathy (DN) [83], LncRNA KCNQ1OT1 can also target miR-214, and regulate ALP, BMP2, Runx2, OPN, and OCN in osteogenesis and related disorders, which may include osteoporosis and periodontitis [84].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine-induced NEAT1 upregulation results in the suppression of its functional target gene, STX17. This phenomenon contributes to the blockage of autophagy flux and the production of inflammation factors within human periodontal ligament stem cells (PDLSCs) [125]. Given the role played by nicotine in the proliferation of human lung tumor cells, a thorough ultrastructural analysis of the effects caused by nicotine in these cells is important.…”
Section: Ultrastructure Of Human Adenocarcinoma Cell Line A549 Treate...mentioning
confidence: 99%
“…In PDLSCs, nicotine has also been shown to impair autophagosome‐lysosome fusion and lysosomal function to block autophagic flux, thereby upregulating the synthesis of inflammatory cytokines and exacerbating periodontal inflammation (Zhang et al, 2023). In addition, studies have demonstrated that nicotine can induce apoptosis of PDLSCs by activating nicotine acetylcholine receptors (nAChRs), resulting in cytotoxic effects (Kim et al, 2012).…”
Section: Effect Of Periodontal Microenvironment On the Death Of Pdlcsmentioning
confidence: 99%